MnTE-2-PyP Attenuates TGF-β-Induced Epithelial-Mesenchymal Transition of Colorectal Cancer Cells by Inhibiting the Smad2/3 Signaling Pathway. (25th February 2019) - Yang, Yu; Zhang, Pei; Yan, Ruicheng; Wang, Qi; Fang, Erhu; Wu, Hongxue; Li, Shijun; Tan, Haiyan; Zhou, Xing; Ma, Xianxiong; Tang, Yu; Huang, Yongming; et al.
Abstract : Background . As a key step in enhancing cancer cell invasion and metastasis, epithelial-mesenchymal transition (EMT) plays an important role in colorectal cancer progression. EMT is triggered by a variety of signaling pathways, among which the transforming growth factor β (TGF- β ) signaling pathway has been implicated as a primary inducer. Accumulating evidence demonstrates that MnTE-2-PyP (chemical name: manganese(III) meso -tetrakis-(N-ethylpyridinium-2-yl), a superoxide dismutase (SOD) mimetic, inhibits TGF- β signaling; however, its ability to inhibit TGF- β -induced EMT in colorectal cancer has not yet been explored. Methods . To verify our hypothesis that MnTE-2-PyP attenuates TGF- β -induced EMT, human colorectal cancer cells were treated with TGF- β in the presence or absence of MnTE-2-PyP. Cells were analyzed by several techniques including western blotting, real-time quantitative PCR, transwell assay, and wound healing assay. Results . MnTE-2-PyP reverses cell phenotypes induced by TGF- β in colon cancer cells. MnTE-2-PyP treatment significantly reduced the expression of mesenchymal markers but maintained epithelial marker expression. Mechanistically, MnTE-2-PyP suppressed the phosphorylated Smad2/3 protein levels induced by TGF- β in SW480 cells, but MnTE-2-PyP failed to suppress TGF- β -induced Slug and Snail expression in colorectal cells. Furthermore, MnTE-2-PyP effectively suppressed TGF- β -mediated cell migration and invasion and the expression of matrix metalloproteinase 2 (MMP-2) and matrix metalloproteinase 9 (MMP-9) in colorectal cells. Conclusion . Taken together, we provide an in-depth mechanism by which MnTE-2-PyP inhibits colorectal cancer progression, supporting an important role for MnTE-2-PyP as an effective and innovative antitumor agent to enhance treatment outcomes in colorectal cancer.